Turning Volcanic Ash into Fertile Soil: Farmers’ Options in Coffee Agroforestry After the 2014 Mount Kelud Eruption - Rizki Maulana Ishaq; Danny Dwi Saputra; Rika Ratna Sari; Didik Suprayogo; Widianto Widianto; Cahyo Prayogo; Kurniatun Hairiah (AGRIVITA, Journal of Agricultural Science, 2020)
Post eruption land reclamation consists of hoeing, mixing volcanic ash with soil, adding external organic and/or in-organic fertilizers and making infiltration-pits (‘rorak’). This study, after the 2014 eruption of Kelud volcano, aimed to evaluate: (a) soil physico-chemical fertility post eruption, (b) impact of organic inputs interacting with ash in infiltration pits on soil C and N underneath (1st experiment), (c) biomass loss (decomposition) of local biomass (Trema orientalis and Parasponia andersonii) in a coffee agroforestry system (2nd experiment). Measurements in the ash-affected (+Ash) Tulungrejo-village (Ngantang-Malang district) were contrasted with an area without recent ash deposits (-Ash) in Krisik (Gandusari-Wlingi district). The 1st experiment (-Ash site) treatments did not lead to statistically significant influences on soil conditions just below the infiltration pits during 12 weeks of monitoring. The 2nd experiment quantified rate of biomass loss from litterbags. In +Ash location, litter half-life time (t50) was 19.5 weeks for coffee or Parasponia as single biomass source to 24 weeks for Coffee+Sengon+Durian. In -Ash location decomposition was slower, with t50 of 24 weeks for Parasponia to 27 weeks for Coffee+Sengon+Durian biomass. Concentrations of soil NH4 and NO3 below the litterbags peaked between 4 to 8 weeks, with nitrification lagging behind on ammonium release.